Adjustable-Loop Femoral Cortical Suspensory Fixation for Patellar Tendon Anterior Cruciate Ligament Reconstruction: A Time Zero Biomechanical Comparison With Interference Screw Fixation. Issue 8 (July 2018) - Mickelson, Dayne T.; Lefebvre, Thomas; Gall, Ken; Riboh, Jonathan C.
Background: Adjustable-loop cortical buttons for femoral fixation of bone-tendon-bone grafts have potential advantages over interference screw fixation; however, these devices have not been benchmarked biomechanically against interference screws. Purpose/Hypothesis: The purpose was to compare the time zero biomechanical properties of commercially available, adjustable-loop cortical button and metallic interference screws for femoral fixation of bone-tendon-bone grafts. It was hypothesized that no significant differences would be found in biomechanical properties between fixation techniques. Study Design: Controlled laboratory study. Methods: Adjustable-loop cortical buttons (n = 8) and metallic interference screws (n = 8) were used to fix matched pairs of human bone-tendon-bone allografts in porcine distal femurs. These constructs were preconditioned (10 N to 50 N at 1 Hz, 10 cycles), subjected to cyclic loading (50 N to 250 N at 1 Hz, 500 cycles), and then pulled to failure at 20 mm/min. Results: The loads to failure (mean ± SD, 700 ± 256 N vs 688 ± 215 N, P = .92) and linear stiffnesses (219 ± 48 N/mm vs 218 ± 49 N/mm, P = .97) for the adjustable-loop cortical button and metallic interference screws, respectively, were not significantly different. Cyclic displacement was higher in the adjustable-loop cortical button group (2.1 ± 0.6 mm vs 1.3 ± 0.4 mm, P = .01). The mechanism of failure was different between groups, with bone block slippage occurring most commonly in the interference screw group (n = 5) and fracture of the bone block through the suture hole occurring most commonly in the adjustable-loop cortical button group (n = 6). Conclusion: Adjustable-loop cortical buttons and interference screws have similar time zero failure loads, although cyclic displacement was higher with the adjustable-loop cortical buttons. The mean difference in displacement was less than 1 mm compared with the interference screw. Clinical Relevance: Adjustable-loop cortical buttons may be an acceptable alternative to an interference screw for femoral fixation of bone-tendon-bone grafts in anterior cruciate ligament reconstruction. The clinical relevance of the observed differences in cyclic displacement is unknown and should be evaluated in future studies.